Deep level transient spectroscopy of CVD diamond: the observation of defect states in hydrogenated films - Gaudin, O; Whitfield, MD; Foord, J; Jackman, R (2001)
Hydrogenated polycrystalline CVD diamond films support a number of defect states within the range 0.03-1.0 eV, as determined by charge-based deep level transient spectroscopy (Q-DLTS). The observation of a 30-meV state is direct evidence for such a shallow level in this material, and is most likely to be the acceptor state that gives rise to the p-type character of these films. Deeper levels, at 0.11 eV, 0.39 eV, 0.65 eV and 0.70 eV-1.0 eV can also be observed and again appear to be associated with the hydrogenation level within the near surface region of the CVD diamond film. The loss of the 0.11 eV level at temperatures greater than 417 K is most easily explained if adsorbates are being removed from the surface at this temperature. © 2001 Elsevier Science B.V. All rights reserved.